Medication box management system with automatic dosing integrated with IoT-based Android app and Firebase - Nurhakim, Raihan; Ath Thahirah Al Azhima, Silmi; Fahmi Arief Hakim, Nurul; Al Qibtiya, Mariya; Maulana, Luthfi; Rohman, Saepul (Institute of Advanced Engineering and Science, 2025)
Utilizing Firebase technology and an Android internet of things (IoT) application, the research endeavors to create a smart medicine box in order to enhance the efficacy of automated drug management. Hardware implementation, software implementation, and 3D design planning for automatic dosage adjustment are the methods utilized. The results prove that the application effectively controls the dosage, evacuation schedule, and quantity of the medication based on the user’s input. Boundary value analysis (BVA) black box testing demonstrated that every feature of the application functions as intended. Furthermore, the efficacy of drug production testing indicates that the smart medicine box exhibits a notable level of precision, albeit with a limited number of inaccuracies that could be rectifiable through additional parameter and mechanism optimizations within the drug box. Consequently, the investigation has effectively produced an automated drug management system that has the potential to enhance drug use supervision and safety, particularly for elderly services individuals residing alone.